Stigma predicts residential treatment length for substance use disorder. (May 2014) - Luoma, Jason B.; Kulesza, Magdalena; Hayes, Steven C.; Kohlenberg, Barbara; Larimer, Mary
Abstract Background: Stigma has been suggested as a possible contributor to the high rates of treatment attrition in substance-dependent individuals, but no published empirical studies have examined this association. Objectives: The present paper assessed the relationship between baseline stigma variables and length of treatment stay in a sample of patients in a residential addictions treatment unit. Methods: The relationship between baseline stigma variables (self-stigma, enacted stigma, and shame) and length of stay for participants (n = 103) in a residential addictions treatment unit was examined. Results: Higher self-stigma predicted longer stay in residential addictions treatment, even after controlling for age, marital status, race, overall mental health, social support, enacted stigma, and internalized shame. However, other stigma variables (i.e. internalized shame, stigma-related rejection) did not reliably predict length of treatment stay. Conclusion: These results are consistent with other findings suggesting that people with higher self-stigma may have a lowered sense of self-efficacy and heightened fear of being stigmatized and therefore retreat into more protected settings such as residential treatment, potentially resulting in higher treatment costs. Specialized clinical interventions may be necessary to help participants cope with reduced self-efficacy and fear of being stigmatized.